Law and the culture of Israel - Mautner, Menachem (Oxford : Oxford University Press, 2011)
For half a century a fierce struggle to shape Israeli culture has been waged in its legal system. Should Israel be a secular liberal state, or governed by traditional Jewish law and culture? Here, Menachem Mautner tells the story of the political struggles to control Israeli law, and through it the culture of Israel itself.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Law -- Israel; Culture and law; Religion and law -- Israel; Law -- Political aspects -- Israel; Law -- Social aspects -- Israel; Israel -- Civilization; Israel -- Religion